2015
DOI: 10.1021/acs.jpca.5b01304
|View full text |Cite
|
Sign up to set email alerts
|

Gas–Solid Reaction Kinetics of ZnFe2O4Formation from 907 to 1100 °C

Abstract: The reaction kinetics of Zn vapor with Fe3O4 (magnetite) were studied from 907 to 1100 °C using a new experimental setup that only allows contact between the reactants through a gas-solid reaction. Hematite was used to create the reaction pellets. Because of the reducing atmosphere in the setup, a magnetite layer is formed on the outside of the pellet, which in turn reacts with the Zn vapor. After reaction, Zn concentration profiles were measured in the reacted magnetite layer using field-emission gun electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…4) [7] can be accounted for. This allows the implementation of the time-temperature profile into the model.…”
Section: Calculation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4) [7] can be accounted for. This allows the implementation of the time-temperature profile into the model.…”
Section: Calculation Methodsmentioning
confidence: 99%
“…We found that, thermodynamically, Zn vapor will react with magnetite to form franklinite (Reaction 1) [6]. In order to understand the impact of this reaction on the composition of the solid particles in the EAF off-gas, the reaction kinetics were studied and diffusion coefficients describing the reaction were found [7].…”
Section: Introductionmentioning
confidence: 99%
“…Through recycling it may be possible to create a product that may be used as an input for a zinc recovery process, through either a pyro-or hydrometallurgical route. In this case, the high iron content and form of the zinc (possibly zinc ferrite) may be a concern for zinc producers [6,7,8]. Hence, knowledge of the form in which the iron and zinc are found within the BOS dust is crucial in understanding how to best recycle the dust or how best to process it for recycling [2,4,5,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of zinc ferrite or a zinc-containing spinel within the sample has been noted in other steel plant byproducts that contain iron and zinc oxides. [21][22][23][24] It should be acknowledged that there were not enough of the zinc bearing phases (zincite and spinel, with a trace amount of zinc hydroxide detected) to account for all of the ZnO content as measured by XRF (Table 1). This "missing" zinc is most likely one of the components of the nonbulk crystalline proportion of the sample.…”
Section: Characterisation Of Unreacted Bos Filter Cakementioning
confidence: 99%